An Evaluation of Manet Performance using AODV by Varying Mobility Speed and Pause Time - Nurul Hidayah Ibrahim (2019)
Mobile Ad-Hoc Network (MANET) is a wireless network that contains a lot of free or autonomous nodes. The nodes in MANET are mobile thus entering and leaving the network consequently change the topology of the network continuously. Therefore, themobility model shows how the speed and direction of a node changed according to a given pattern of mobility. The most common mobility model used by the researcher is Random Waypoint model because it is easy to implement and imitate with the real scenario. Real scenario environment involves random movement of mobile thus mobility of the nodes can largely affect the performance of routing protocol. These recent years, various routing protocols are targeted specifically for this environment and it has been developed with some performance simulation and analyzation. Generally, there are 3 types of routing protocol: proactive, reactive and hybrid. This project will be focusing on AODV which is a reactive routing protocol. AODV is on-demand routing where the routes will be created only when it is required to send the packets. The performance of AODV is analyzed by varying mobility speed with different pause times. Performance metrics considered in the study are throughput, packet delay, and packet delivery ratio (PDR). .